Copyright, Information and Education - Bosumprah, Bernard K. (Ghana Library Journal, 2011)
The purpose of the subject matter of Copyright is protection of culture or the cultural industries. No civilized human society can live without protecting its cultural products such as books, music and painting. The literature, music andartistic output of a country and their interpretations by actors, singers, dancers and others constitute the culture of that country and form perhaps the most important part of its national identity.